Antiaging effects of the mixture of Panax ginseng and Crataegus pinnatifida in human dermal fibroblasts and healthy human skin - Hwang, Eunson; Park, Sang-Yong; Yin, Chang Shik; Kim, Hee-Taek; Kim, Yong Min; Yi, Tae Hoo (Journal of ginseng research, 2017)
Human skin undergoes distinct changes throughout the aging process, based on both intrinsic and extrinsic factors. In a process called photoaging, UVB irradiation leads to upregulation of matrix metalloproteinase-1, which then causes collagen degradation and premature aging. Mixtures of medicinal plants have traditionally been used as drugs in oriental medicine. Based on the previously reported antioxidant properties of Panax ginseng Meyer and Crataegus pinnatifida, we hypothesized that the mixture of P. ginseng Meyer and C. pinnatifida (GC) would have protective effects against skin aging. Anti-aging activity was examined both in human dermal fibroblasts under UVB irradiation by using Western blot analysis and in healthy human skin by examining noninvasive measurements. In vitro studies showed that GC improved procollagen type I expression and diminished matrix metalloproteinase-1 secretion. Based on noninvasive measurements, skin roughness values, including total roughness (R1), maximum roughness (R2), smoothness depth and average roughness (R3), and global photodamage scores were improved by GC application. Moreover, GC ameliorated the high values of smoothness depth (R4), which means that GC reduced loss of skin moisture. These results suggest that GC can prevent aging by inhibiting wrinkle formation and increasing moisture in the human skin.